2023
DOI: 10.1001/jamanetworkopen.2023.43781
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Corticosteroid Treatment During the Late-Preterm Period and Neonatal Outcomes for Twin Pregnancies

Jie Zhu,
Ying Zhao,
Ping An
et al.

Abstract: ImportanceAntenatal corticosteroid treatment of individuals with singletons at risk for delivery during the late-preterm period has been academically recommended. However, the evidence on the use of antenatal corticosteroid treatment for twins at risk for delivery during the late-preterm period is still lacking.ObjectiveTo evaluate whether antenatal corticosteroid treatment during the late-preterm period in twin pregnancies was associated with a lower risk of newborn morbidity.Design, Setting, and Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Only 30% of the infants received a complete course of ANS in their study as compared to 74% infants receiving a complete course in our study. Cesarean delivery was reported in 3.5% of the deliveries in their study compared to 68.8% of the deliveries in the current study (22).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Only 30% of the infants received a complete course of ANS in their study as compared to 74% infants receiving a complete course in our study. Cesarean delivery was reported in 3.5% of the deliveries in their study compared to 68.8% of the deliveries in the current study (22).…”
Section: Discussioncontrasting
confidence: 63%
“…Among LPT multiple gestation infants, the limited evidence from retrospective studies has noted no signi cant reduction in respiratory morbidities in infants with ANS exposure (21) (22). The American College of Obstetricians and Gynecologists (ACOG) recommends a single course of betamethasone for women between 34 0/7 weeks and 36 6/7 weeks who are at risk for delivery within 7 days and who have not previously received ANS.…”
Section: Introductionmentioning
confidence: 99%
“…And the study by Zhu et al (17) ; a total of 1974 twin pregnancies who were at risk for late preterm labor (34 weeks to 36 weeks and 6 days of gestation) were included in this research of twin pregnancies delivered in a university-affiliated hospital in China. Another study found that in spite of the proven effect in singletons it is not proved in twins.…”
Section: Interpretation Of the Current Findings And Comparison To Sim...mentioning
confidence: 99%